Current state, sources, and potential risk of heavy metals in sediments of Three Gorges Reservoir, China. (July 2016) - Bing, Haijian; Zhou, Jun; Wu, Yanhong; Wang, Xiaoxiao; Sun, Hongyang; Li, Rui
Abstract: Heavy metal (HM) contamination in sediments of Three Gorges Reservoir (TGR) is a particularly important issue for the safety of water quality due to the potential threats of metal toxicity to local and downstream human health. Surface sediments from riparian and submerged areas in the entire TGR mainstream were collected in 2014 to investigate the spatial distribution of HMs (Cd, Cu, Pb, and Zn), identify their possible sources, and assess their potential risk by multiple indices and metal fraction. Results showed that the concentrations of HMs in the sediments increased after the TGR operation, but were lower than those in other Chinese rivers of developed areas. The acid-soluble Cd accounted for more than 50% of total Cd in the sediments, whereas that of other HMs was very low. The Cd concentrations in the riparian sediments increased towards the dam; however, other metals in the riparian sediments and all HMs in the submerged sediments did not show any regular variation trend spatially. The stocks of HMs were significantly higher in the submerged sediments than in the riparian sediments. The high accumulation of HMs in the riparian sediments emerged between Fuling and Fengjie, and those in the submerged sediments existed in the near dam areas. Grain size and Fe/Mn oxides controlled the mobility and transfer of HMs in the sediments. Human activity in the catchment including industrial and agricultural production, shipping industry, mining, etc., increased inputs of HMs in the sediments, and altered their spatial distribution patterns. The sediments were moderately to highly contaminated by Cd, and slightly contaminated by other HMs. The results indicate the current priority of Cd contamination in the TGR, and will conduce to ecological protection in the TGR region. Graphical abstract: Highlights: Distribution of Cd, Cu, Pb and Zn in sediments of the entire TGR mainstream was investigated. HMs stocks concentrated in middle riparian zones and near dam submerged areas. Sediment grain size and chemical conditions determined HMs mobility. TGR operation and local human activity controlled HMs distribution in sediments. TGR mainstream sediments were moderately to highly contaminated by Cd. Abstract : Human activity in the catchment of Three Gorges Reservoir increased heavy metal accumulation in the riparian and submerged sediments.